Bringing H2AX into the angiogenesis family. - Rankin, E; Giaccia, A; Hammond, E (2009)
The cell's ability to sense and respond to DNA damage is critical to maintain homeostasis and prevent the development of cancer. Paradoxically, Economopoulou et al. recently reported that a DNA damage response protein, H2AX, promotes tumor growth and angiogenesis.